Women and the Mbojo Weaving in Nusa Tenggara Barat: Position and role - Muh Mizan,; Ningsih, Aria (Technium Social Sciences Journal, 2022)
This study aims to explain the problems has related to the aesthetics of Mbojo weaving at West Nusa Tenggara and also related the position and role of women in its development. Women are considered to have very strong interactions with the latest aesthetic elements and the continuity of Mbojo's weaving. To obtain results of this research, the author uses qualitative analysis methods with a multidisciplinary approach, the cultural theory, aesthetic approaches, and the concepts of gender. The results showed that Mbojo weaving has never been separated from the role of women. This is because all activities related to the production process, starting from determining aesthetic elements, product management and distribution of weaving products, are fully managed and become the authority of women craftsmen. Triggered by the cultural paradigm of society that weaving is indeed a job that is only done by women. When viewed from the point of view of the slow development of the motives, it shows that Mbojo weaving still follows the traditional pattern. This indirectly becomes its own character and uniqueness for Mbojo weaving, so that its shape can be distinguished from weaving in other areas.